2004
DOI: 10.1158/1078-0432.ccr-03-0774
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1 Is a Novel Therapeutic Target for Human Sarcoma

Abstract: Purpose: Little is known about the role that Mcl-1, an antiapoptotic Bcl-2 family member, plays in solid tumor biology and susceptibility to anticancer therapy. We observed that the Mcl-1 protein is widely expressed in human sarcoma cell lines of different histological origin (n ‫؍‬ 7). Because the expression of antiapoptotic Bcl-2 family proteins can significantly contribute to the chemoresistance of human malignancies, we used an antisense strategy to address this issue in sarcoma.Experimental Design: SCID m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 55 publications
2
48
1
Order By: Relevance
“…To determine whether reduced Mcl-1 expression will sensitize cells to etoposide-induced apoptosis, antisense oligonucleotides against Mcl-1 were transfected into MDA-MB-231 cells and the amount of etoposide-induced apoptosis was determined. Previously, we and other have shown that antisense oligonucleotides against Mcl-1 were specific for Mcl-1 and not other Bcl-2 family members (14,22,23). Etoposide treatment alone induced 18% apoptosis, whereas antisense, sense, and scrambled oligonucleotides against Mcl-1 failed to induce apoptosis.…”
Section: Resultsmentioning
confidence: 66%
“…To determine whether reduced Mcl-1 expression will sensitize cells to etoposide-induced apoptosis, antisense oligonucleotides against Mcl-1 were transfected into MDA-MB-231 cells and the amount of etoposide-induced apoptosis was determined. Previously, we and other have shown that antisense oligonucleotides against Mcl-1 were specific for Mcl-1 and not other Bcl-2 family members (14,22,23). Etoposide treatment alone induced 18% apoptosis, whereas antisense, sense, and scrambled oligonucleotides against Mcl-1 failed to induce apoptosis.…”
Section: Resultsmentioning
confidence: 66%
“…Remarkably, these observations are in contrast to previous studies for solid tumors, where silencing of Mcl-1 by itself did not reveal a significantly altered phenotype. 31,38 This finding highlights the biological relevance of Mcl-1 for gastric cancer. Such a prominent role for Mcl-1 expression for cell survival has been reported so far primarily for hematological malignancies like myeloma and leukaemia.…”
Section: Discussionmentioning
confidence: 67%
“…Western blotting of lysed cells for Mcl-1 and Tubulin was performed as described previously. 31 In brief, whole cell extracts were prepared using 0.14 M NaCl, 0.2 M Triethanolamine, 0.2% Na-deoxycholate, and 0.5% Nonidet P-40, supplemented with protease inhibitors (all Sigma, St. Louis, MO, USA). Ten micrograms of total protein were separated on SDS-PAGE and blotted to PVDF membranes (Tropix, Bedford, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Because Mcl-1 is well known as an antiapoptotic protein, it might be expected that Mcl-1 would be expressed at higher levels in patients with a worse response to radiotherapy and chemotherapy (27,41).…”
Section: Discussionmentioning
confidence: 99%